Complete Solution of an Inverse Problem for One Class of the High Order Ordinary Differential Operators with Periodic Coefficients - Efendiev, R. F. (Журнал математичної фізики, аналізу, геометрії, 2006)
The purpose of the present work is to solve the characterization problem, which consists of identification of necessary and sufficient conditions on the scattering data ensuring that the reconstructed potential belongs to particular class.Mathematics Subject Classification: 34B25, 34L05, 34L25, 47A40, 81U40.